The Philippines: The quest for genuine e-development - Ona, Sherwin E. (Animo Repository, 2012)
After more than a hundred years of independence and its outstanding growth performance during the 1950s and the 1960s, the Philippines today has been regarded as a perennial development laggard—unable to achieve sustained economic growth thus earning the label of an “antidevelopment state.” The country faces numerous development challenges. In this chapter we analyze recent and ongoing efforts to break the antidevelopment cycle by harnessing information and communication technologies (ICT). We review selected ongoing Philippine ICT for development (ICT4D) initiatives and the characteristics of these initiatives. We classify these initiatives as “traditional”—disjointed, unsustainable, and short-term oriented.